2014
DOI: 10.1097/tp.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term TNF-Alpha Inhibition Reduces Short-Term and Long-Term Inflammatory Changes Post-Ischemia/Reperfusion in Rat Intestinal Transplantation

Abstract: Infliximab significantly reduced both acute IRI and, as with other TNFα inhibitors, long-term inflammatory responses after rat ITX. TNFα inhibition may help diminish chronic inflammatory long-term effects and avoid chronic allograft enteropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 30 publications
0
11
1
1
Order By: Relevance
“…In recent studies, the inflammatory gene expression profiling of injured mouse kidney revealed a significant severity-and time-dependent association of the inflammatory pathway with AKI [13]. TNF-α inhibitors decreased inflammatory changed after IRI [14]. In a HgCl 2 -induced AKI mice model, IL-19 expression was high in the kidney [15].…”
Section: Discussionmentioning
confidence: 97%
“…In recent studies, the inflammatory gene expression profiling of injured mouse kidney revealed a significant severity-and time-dependent association of the inflammatory pathway with AKI [13]. TNF-α inhibitors decreased inflammatory changed after IRI [14]. In a HgCl 2 -induced AKI mice model, IL-19 expression was high in the kidney [15].…”
Section: Discussionmentioning
confidence: 97%
“…Grafts were gently manipulated since organ manipulation per se induces substantial inflammatory changes . In the last six patients, anti‐TNFα was administered given its protective effect against intestinal ischemia–reperfusion injury . Interestingly, TNFα inhibition has been demonstrated to restore Tregs levels and function in rheumatoid arthritis patients .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of cytokines and chemokines are detected in gut tissue, lymph draining the intestine, and plasma following intestinal I/R, including TNF-a, IL-1b, Il-6, IL-8, IL-10, MIP-1, and KC (183,348,423,467,538). With the exception of IL-10, these cytokines promote the recruitment of leukocytes in postischemic tissue, and experimental interventions directed toward immunoneutralization or genetic deletion of specific cytokines have been shown to blunt the inflammatory response to gut I/R (124,156,348,536). The appearance of the cytokines in postischemic tissue parallels the increased expression of endothelial cell adhesion molecules like E-selectin (124,416).…”
Section: Consequences and Mechanisms Of Ischemic Injurymentioning
confidence: 98%